2022
DOI: 10.1021/acsnano.2c02031
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Thermal-Assisted Spin–Orbit Torque-Induced Magnetization Switching for Energy-Efficient Logic-in-Memory

Abstract: Spin–orbit torque (SOT) is widely considered as an effective route to manipulate magnetic order in spintronic devices. The low power consumption and long endurance demands from future computer architectures urgently require a reduction of the critical SOT switching current density, j sw. However, except for searching for a SOT source with a high-spin Hall angle, few efficient mechanisms to reduce j sw have been proposed. In this work, we achieved an anomalous thermal-assisted (TA) j sw reduction in a Pt/Co/Tb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Here, the θ SH of our system is determined as well as the value of H x , so that the change in I c could be mainly attributed to the variation of H k . The decrease in H k with temperature in Figure e verifies the conclusion that I c decreases with an increase in temperature, and this phenomenon has been discussed in several reports. …”
Section: Temperature-dependent Sot Switchingmentioning
confidence: 89%
See 1 more Smart Citation
“…Here, the θ SH of our system is determined as well as the value of H x , so that the change in I c could be mainly attributed to the variation of H k . The decrease in H k with temperature in Figure e verifies the conclusion that I c decreases with an increase in temperature, and this phenomenon has been discussed in several reports. …”
Section: Temperature-dependent Sot Switchingmentioning
confidence: 89%
“…This suggests that magnetization reversal occurs step by step in many small domains, each with a different deterministic J c . Therefore, we can achieve multistate magnetoresistance by adjusting the amplitude and width of the current pulses, promising possible application in multistate storage or other logic devices. ,, …”
Section: Flexible Device With a Reduced Sot Switching Currentmentioning
confidence: 99%
“…Since temperature varies on the same timescale as the magnetization switching, the net magnetization and angular momentum are dynamical quantities. Therefore, one or both compensation temperatures may be reached and overcome during the switching, [140,141] and assessing the importance of the two compensation points is challenging.…”
Section: Magnetization Switchingmentioning
confidence: 99%
“…In particular, SOT-based reconfigurable logic devices are expected to provide solutions for ultralow-power, high-speed, high-density, and non-volatile systems. These devices can also perform multiple logic operations in a single device frame, enhancing their efficiency compared to conventional logic devices 21 29 . For example, numerous studies of spin-based reconfigurable logic devices have also reported successful logic operations using skyrmion dynamics, magnetic tunnel junctions, and chirality-based vortex domain walls 30 34 .…”
Section: Introductionmentioning
confidence: 99%